1996
DOI: 10.1002/(sici)1097-4652(199608)168:2<229::aid-jcp1>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of changes in cytosolic Ca2+ and Na+ concentrations in rat submandibular gland acini exposed to carbachol and ATP

Abstract: The relationship between cytosolic concentrations of Ca2+ (Ca2i) and Na+ (Na+i) were studied in preparations of rat submandibular and pancreatic acini loaded with the Ca(2+)-sensitive dye Fura-2 or the Na(+)-sensitive dye SBFI. Pancreatic acini showed no changes in Na+i during either transient or persistent changes in Ca2+i. Increases in Ca2+i produced by exposure of submandibular gland acini to carbachol, a muscarinic cholinergic agonist, were followed by an increase in Na+i after a delay of 5-10 s. When Ca2+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…These cations apparently pass through a common influx pathway, since 45Ca2+ uptake (Soltoff et al, 1992) as well as depolarization mediated by Ca2+ entry (Tenneti and Talamo, 1993) is enhanced in the absence of Na+, suggesting that they are competitive. A similar pattern for Na+ and Ca2+ entry was found in ATPstimulated submandibular acini, using 45Ca2+ uptake studies and the Na+-sensitive fluorescent dye, SBFI (M6tioui et al, 1994;Hurley et al, 1996). Further evidence identifying the P2X7 receptor as a component responsible for the P2Z response in rat parotid cells is provided by reverse-transcription/polymerase chain-reaction (RT-PCR) experiments, which demonstrate mRNA for P2X7 receptors in gland extracts (Tenneti et al, 1998).…”
Section: (111) P2 Receptor Subtypes and Function In Salivary Glandsmentioning
confidence: 72%
See 1 more Smart Citation
“…These cations apparently pass through a common influx pathway, since 45Ca2+ uptake (Soltoff et al, 1992) as well as depolarization mediated by Ca2+ entry (Tenneti and Talamo, 1993) is enhanced in the absence of Na+, suggesting that they are competitive. A similar pattern for Na+ and Ca2+ entry was found in ATPstimulated submandibular acini, using 45Ca2+ uptake studies and the Na+-sensitive fluorescent dye, SBFI (M6tioui et al, 1994;Hurley et al, 1996). Further evidence identifying the P2X7 receptor as a component responsible for the P2Z response in rat parotid cells is provided by reverse-transcription/polymerase chain-reaction (RT-PCR) experiments, which demonstrate mRNA for P2X7 receptors in gland extracts (Tenneti et al, 1998).…”
Section: (111) P2 Receptor Subtypes and Function In Salivary Glandsmentioning
confidence: 72%
“…More likely, the inhibition is due in large part to an allosteric modification of agonist binding to the receptor . Crit Rev Oral Biol Med mobilization of Ca2+ by muscarinic, a.-adrenergic, or substance P agonists in rat submandibular gland acini (Hurley et al, 1994(Hurley et al, , 1996Metioui et al, 1996) and mobilization of Ca2+ by muscarinic receptors in rat parotid acini (Jorgensen et al, 1995). The inhibitory effects of ATP do not appear to be due to interference with binding of autonomic transmitters to their receptors (Hurley et al, 1993).…”
Section: (111) P2 Receptor Subtypes and Function In Salivary Glandsmentioning
confidence: 99%
“…This result suggested that ATP might regulate both phases of secretion. In acini, ATP increased the intracellular concentration of Na ϩ (19), activated the Na ϩ /H ϩ exchanger, and opened a chloride channel (20). It also inhibited the response to agonists activating the L-␣-phosphatidylinositol 4,5-bisphosphate-selective phospholipase C (21).…”
mentioning
confidence: 99%
“…Since mitochondrial membrane depolarization can still be observed in the absence of calcium and since the activation of P2X 7 receptors is known to provoke an influx of sodium in salivary glands [31,32], we tested if sodium could be implicated in this process (Fig. 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…To this end extracellular sodium was replaced by NMDG. In order to avoid a massive and probably toxic increase (up to 2 μM) of the [Ca 2+ ] i after exposure of the cells to ATP in the absence of extracellular sodium [31,33], these experiments were performed in the absence of extracellular calcium. Replacement of extracellular sodium by NMDG reduced the mitochondrial membrane depolarization induced by 1 mM ATP by almost 90% (from 33.0 ± 2% to 5.5 ± 2% depolarization after 10 min, n = 3, Fig.…”
Section: Resultsmentioning
confidence: 99%